The association between hospital care transition planning and timely primary care follow‐up. Issue 3 (10th June 2021) - Mitchell, Jordan; Probst, Janice; Li, Xiao
Abstract: Purpose: To determine whether Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) Care Transitions (CTM‐3) Scores were associated with timely (14‐day) primary care provider (PCP) follow‐up visits, and to look for disparities across various types of urban and rural hospitals. Methods: Data were obtained for 3, 299 hospitals: 2, 000 urban, 544 micropolitan prospective payment system (PPS), 109 micropolitan critical access hospital (CAH), 252 noncore rural PPS, and 394 noncore rural CAH. HCAPPS data were drawn from CMS Hospital Compare (2015). The dependent variable, 14‐day PCP follow‐up rate for each hospital, was drawn from the 2015 Dartmouth Atlas. Findings: In analysis adjusting only for hospital characteristics, higher CTM‐3 scores were positively associated with PCP follow‐up; however, the relationship was no longer significant after controlling for area‐level (contextual) measures, such as percent minority population, percent unemployed, and percent uninsured. In the fully adjusted model, rates of PCP follow‐up were significantly higher for micropolitan PPS, noncore PPS, and noncore CAH hospitals than for urban hospitals. Conclusions: In fully adjusted analysis, the lack of significance between CTM‐3 scores and PCP follow‐up suggests that community characteristics facilitate or impede timely PCP follow‐up to an extent that may overshadow in‐hospital efforts. Disparities between CAHs and rural PPS hospitals may be due to differing enrollments in quality incentive plans; future research is needed to address this issue. Compounding this issue, the strong negative relationship between percent Medicaid reimbursement (payor mix) and PCP follow‐up suggests possible disparities for safety net hospitals.